The Effectiveness of Pictionary Game in Teaching Vocabulary of the Fifth grade students at SD Negeri 137 OKU - Nida Fitri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
The problem of this study was concerned to improve the fifth grade students’ vocabulary at SD Negeri 137 OKU by using Pictionary game. The objective of this study was to find out whether it was significantly effective or not using Pictionary game in teaching vocabulary of the fifth grade students atSD Negeri 137 OKU. In this study, the writer used pre experimental method, and its population of this study was all of the fifth grade students of SD Negeri 137 OKU, the total of population was 46 students. In this case, the writer took the sample of the fifth grade students consisted 22 students. The written test in multiple choice form were used as the techniques for collecting the data. The students’ mean score of pre-test class was 51,8 and the students’ mean score of post-test was 72.2. it meant that the fifth grade students’ vocabulary at SD Negeri 137 OKU by using Pictionary game were improved. Based on the result of the students’ mean score above, it meant that it was significant improvement fifth grade students who are taught by using Pictionary game at SD Negeri 137 OKU.